Desarrollo de la motricidad fina y su incidencia en la escritura de los niños con trastorno de déficit de atención en el tercer grado en la unidad educativa José Domingo de Santistevan - Larriva Obregón, María Fernanda (2018)
The child with ADD is characterized by an inadequate development of the attention, activity and impulse control functions affecting the academic and social development of the person. It occurs in all socio-economic strata, levels of education or intelligence degrees. All these symptoms interfere in some way with the normal performance of children with ADD in their school life. Starting from the predominant motor characteristics in children with ADD, it shows the existence of a high proportion of children with this deficit that present difficulties in fine motor development, the difficulties would be manifested in tasks that involve grabbing objects (such as the fork and knife), buttoning clothes, playing with a ball, coloring within the limits of the figure, writing on lines or in a uniform size, or executing writing with acceptable handwriting and completing the written work in the classroom. (Bauermeister, 2002)………